Gender planning and development : theory, practice, and training - Moser, Caroline O. N. (Routledge, 1993)
Exploring the relationship between gender and development, this looks at gender policy and planning practices based on creating gender awareness and negotiation for women's needs at household, civil society, state and global levels.